Effects of 4 Weeks of Active Exergames Training on Muscular Fitness in Elderly Women. Issue 2 (February 2022) - Gallardo-Meza, Cristian; Simon, Kristel; Bustamante-Ara, Natalia; Ramirez-Campillo, Rodrigo; García-Pinillos, Felipe; Keogh, Justin W.L.; Izquierdo, Mikel
Abstract : Abstract: Gallardo-Meza, C, Simon, K, Bustamante-Ara, N, Ramirez-Campillo, R, García-Pinillos, F, Keogh, JWL, and Izquierdo, M. Effects of 4 weeks of active exergames training on muscular fitness in elderly women. J Strength Cond Res 36(2): 427–432, 2022—To analyze the effects of 4 weeks of an active exergames training program on muscular fitness in older women, 2 groups of community dwelling physically active subjects were formed by block-design randomization. One was deemed the control group (CG, n = 37; age 68.1 ± 3.3 years), and a second group completed 4 weeks of an active exergames training program (ExG, n = 35; age, 69.2 ± 3.7 years). Training included active exergames (Wii Fit Plus) performed on the Wii Balanceboard, 2 sessions per week. The exergames required mainly balance-related movements, such as leaning forward, leftward, and rightward, also requiring isometric squat positions and explosive leg extension. A supervisor-to-subject ratio method of 2:1 was used. An intensity-based individual progressive overload was applied. There were no significant (all p > 0.05, d = 0.01–0.07) baseline differences between-groups for all dependent variables. For the ExG, significant improvements were observed in static balance right leg test (Δ75.5%, d = 0.89), static balance left leg (Δ33.7%, d = 0.57), timed up-and-go test (Δ14.8%, d = 0.85) and sit-to-stand velocity test (Δ83.8%, d = 1.62). For the control group, trivial to small decrements in performance were observed across all tests (Δ −2.1 to −8.4%, d = −0.08 to 0.32). Group × time interactions were observed for the static balance right and left leg, timed up-and-go test, and the mean velocity achieved in the 5-repetition sit-to-stand test (all p < 0.001; d = 0.33–0.60). In conclusion, exergames training improves muscular fitness in older women. These results should be considered when designing appropriate and better exercise training programs for older women.